Quantification of cells with specific phenotypes I: Determination of CD4+ cell count per microliter in reconstituted lyophilized human PBMC prelabeled with anti‐CD4 FITC antibody. (5th February 2015) - Stebbings, Richard; Wang, Lili; Sutherland, Janet; Kammel, Martin; Gaigalas, Adolfas K.; John, Manuela; Roemer, Bodo; Kuhne, Maren; Schneider, Rudolf J.; Braun, Michael; Engel, Andrea; Dikshit, Dinesh K.; et al.
Abstract A surface‐labeled lyophilized lymphocyte (sLL) preparation has been developed using human peripheral blood mononuclear cells prelabeled with a fluorescein isothiocyanate conjugated anti‐CD4 monoclonal antibody. The sLL preparation is intended to be used as a reference material for CD4+ cell counting including the development of higher order reference measurement procedures and has been evaluated in the pilot study CCQM‐P102. This study was conducted across 16 laboratories from eight countries to assess the ability of participants to quantify the CD4+ cell count of this reference material and to document cross‐laboratory variability plus associated measurement uncertainties. Twelve different flow cytometer platforms were evaluated using a standard protocol that included calibration beads used to obtain quantitative measurements of CD4+ T cell counts. There was good overall cross‐platform and counting method agreement with a grand mean of the laboratory calculated means of (301.7 ± 4.9) μL−1 CD4+ cells. Excluding outliers, greater than 90% of participant data agreed within ±15%. A major contribution to variation of sLL CD4+ cell counts was tube to tube variation of the calibration beads, amounting to an uncertainty of 3.6%. Variation due to preparative steps equated to an uncertainty of 2.6%. There was no reduction in variability when data files were centrally reanalyzed. Remaining variation was attributed to instrument specific differences. CD4+ cell counts obtained in CCQM‐P102 are in excellent agreement and show the robustness of both the measurements and the data analysis and hence the suitability of sLL as a reference material for interlaboratory comparisons and external quality assessment. © 2015 The Authors. Published by Wiley Periodicals, Inc.